2018
DOI: 10.1104/pp.17.01687
|View full text |Cite
|
Sign up to set email alerts
|

The Extra-Pathway Interactome of the TCA Cycle: Expected and Unexpected Metabolic Interactions

Abstract: The plant tricarboxylic acid (TCA) cycle provides essential precursors for respiration, amino acid biosynthesis, and general nitrogen metabolism; moreover, it is closely involved in biotic stress responses and cellular redox homeostasis. To further understand the in vivo function of the TCA cycle enzymes, we combined affinity purification with proteomics to generate a comprehensive extra-pathway protein-protein interaction network of the plant TCA cycle. We identified 125 extra-pathway interactions in Arabidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 63 publications
3
68
1
Order By: Relevance
“…Second, more recently, both in vitro and reverse genetic studies have revealed an important role for the mitochondrial (and cytosolic) thioredoxin system in the regulation of the TCA cycle, through deactivating both succinate dehydrogenase and fumarase, as well as upregulating the cytosolic enzyme adenosine triphosphate (ATP)‐citrate lyase (Schmidtmann et al ; Daloso et al ; Geigenberger et al ). Third, a range of contemporary molecular and cell biology approaches have revealed that the plant TCA cycle (Zhang et al ; Zhang et al ), like that of microbial (Meyer et al ) and mammalian (Robinson and Srere ) systems, form dynamic enzyme assemblies or metabolons. Indeed, the metabolon concept was established on studying the TCA cycle in rat liver, with the impetus to look for such an enzyme assembly being the fact that the levels of organic acids, within this tissue, were not consistent with the properties of the enzymes when evaluated in isolation (Srere ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, more recently, both in vitro and reverse genetic studies have revealed an important role for the mitochondrial (and cytosolic) thioredoxin system in the regulation of the TCA cycle, through deactivating both succinate dehydrogenase and fumarase, as well as upregulating the cytosolic enzyme adenosine triphosphate (ATP)‐citrate lyase (Schmidtmann et al ; Daloso et al ; Geigenberger et al ). Third, a range of contemporary molecular and cell biology approaches have revealed that the plant TCA cycle (Zhang et al ; Zhang et al ), like that of microbial (Meyer et al ) and mammalian (Robinson and Srere ) systems, form dynamic enzyme assemblies or metabolons. Indeed, the metabolon concept was established on studying the TCA cycle in rat liver, with the impetus to look for such an enzyme assembly being the fact that the levels of organic acids, within this tissue, were not consistent with the properties of the enzymes when evaluated in isolation (Srere ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we suggest using a GFP tag for the bait protein, which facilitates the detection of the protein localization by confocal microscopy (Dunham, Mullin, & Gingras, ; Keilhauer, Hein, & Mann, ). The efficiency of the trypsin digestion and the recovery of the resulting digested peptides for MS analysis are very important for the success of AP‐MS (Zhang, Swart, et al., ). Instead of in‐gel digestion for performing global proteomics profiling (Huang et al., ; Van Leene et al., ), several studies have used the improved efficiency of in‐solution digestion on the beads, reducing time and steps (León, Schwämmle, Jensen, & Sprenger, ; Zhang, Sun, et al., ).…”
Section: Commentarymentioning
confidence: 99%
“…The 38 mitochondrial proteins of Arabidopsis thaliana were transformed into a PSB-D Arabidopsis plant cell culture, and a GFP-tagbased modified AP-MS procedure was implemented based on at least three biological replicates (Zhang, Beard, et al, 2017;Zhang, Swart, et al, 2018). Unlike normal AP-MS in which the gel is cut into pieces for several independent trypsin digestions (Morris et al, 2014), we used a proteomics-based in-solution digestion method to directly digest the proteins on the beads following affinity purification (Zhang, Sun, et al, 2017).…”
Section: Tca Cycle Interaction Networkmentioning
confidence: 99%
See 2 more Smart Citations